Species Diversity and Distribution of Ticks (Acari: Ixodidae) in Zabol County, Eastern Iran. - Maryam Ganjali; Mansour Dabirzadeh; Masoud Sargolzaie (Tehran University of Medical Sciences, 2014)
Background: Ticks are important vectors of human and animal pathogens. They are considered as main vectors fortransmission of many viral, bacterial, rickettsial and parasitical pathogens. The aim of the present study was to find out species diversity of ticks, which infested the domestic ruminants in Zabol County, Eastern Iran in 2012. Methods: Ticks were selected randomly from sheep, goats, cattle and camels. The ticks were collected from the body of infested animals and stored in 70% ethanol, then transported to the laboratory of Zabol University of Medi- cal Sciences. Following examinations under stereomicroscope, ticks were identified using available taxonomic keys. Results: In this study, a total number of 469 adult ticks (381 males and 88 females) were collected. Ticks were clas- sified into 2 genera and 9 species including: Hyalomma dromedarii (17.3%), Hy. schulzei (1.8%), Hy. marginatum (0.5%), Hy. anatolicum excavatum (12.60%), Hy. anatolicum anatolicum (11.2%), Hy. asiaticum asiaticum (11.0%), Rhipicephalus sanguineus (21.2%), Rh. bursa (10.2%) and  Rh. turacunis (13.911%). The frequency of  genus Hyalomma (54.6%) was higher than Rhipicephalus. Rh. sanguineus was the predominant tick species and accounted for 21.26% of the ticks. The ratio of males was more than the female ticks. Conclusion: Hyalomma and Rhipicephalus spcies are commonly distributed in the study area. Further investiga- tions are needed to identify the role of above tick species as vectors of pathogenic organisms.